Hybrid Enhanced Tabu Search with Elite-Based Restart for Cost-Driven Optimal Power Flow with Discrete Controls - Pezo, Anthony [UNESP]; Dominguez, Ines C. [UNESP]; Romero, Rubén [UNESP]; Possagnolo, Leonardo Henrique Faria Macedo (Institute of Electrical and Electronics Engineers (IEEE), 2025)
This paper presents a hybrid optimization approach for the optimal power flow problem using an enhanced tabu search integrated with the KNITRO solver. The method handles binary and integer variables, including discrete tap settings and shunt statuses, while continuous variables are optimized via nonlinear programming. A memory-efficient elitebased restart strategy and path-relinking intensification are proposed to enhance global exploration and convergence speed. The performance of the proposed approach is validated on the IEEE 14-, 30-, 57-, and 118-bus systems, demonstrating its effectiveness in finding high-quality solutions when compared to traditional mixed-integer nonlinear programming solvers.